Trends in body mass index, overweight and obesity among adults in the USA, the NHANES from 2003 to 2018: a repeat cross-sectional survey - Zhe Li; Mingxi Li; Weijun Gong; Shidong Wang (BMJ Open)
Objectives To analyse detailed trends in adult obesity from 2003 to 2018 in the USA, and provide the latest national estimates of adult obesity in 2017–2018.Design, setting and participants Analysis of data, including measured height and weight, obtained from 42 266 adults aged ≥20 years from the National Health and Nutrition Examination Survey, a cross-sectional, nationally representative sample of the US population.Exposure Survey period.Primary outcome measures The mean body mass index (BMI) and prevalence of overweight and obesity.Results In 2017–2018, the prevalence of overweight (including obesity, BMI ≥25 kg/m2) and obesity (BMI ≥30 kg/m2) was 73.8% (95% CI 71.1% to 76.4%) and 42.8% (95% CI 39.5% to 46.1%), respectively. From 2003 to 2018, a significant increase in the prevalence of overweight (including obesity, overall adjusted OR for 2017–2018 vs 2003–2004, 1.08 (95% CI 1.04 to 1.13) and obesity (overall adjusted OR for 2017–2018 vs 2003–2004, 1.15 (95% CI 1.10 to 1.21) was found among American adults. However, annual changes in mean BMI and the prevalence of overweight and obesity did not differ significantly before and after 2009–2010. The prevalence of overweight and obesity varied significantly by age, sex, race, education, daily total energy intake, economic conditions and physical activity status (all p<0.05).Conclusions Although the prevalence of adult obesity continues to rise, there have been no significant changes in the annual growth of adult obesity prevalence between 2003–2004 and 2017–2018. In 2017–2018, the prevalence of obesity was 42.8%, which equates to 76 million American adults at risk for serious and costly chronic conditions. The prevalence of obesity was higher among older adults (aged 60–69 years), females, non-Hispanic blacks, and those who did not graduate college, were physically inactive, reported lower daily total energy intake and had poor economic status.